2012
DOI: 10.1093/rpd/ncs278
|View full text |Cite
|
Sign up to set email alerts
|

Microdosimetry of X-ray-irradiated gold nanoparticles

Abstract: The use of contrast agents, particularly those made of high atomic number elements like gold nanoparticles, to enhance the X-ray absorption properties of tissue has recently gained attention in the context of radiotherapy treatments. Because these contrast agents alter the secondary electron field in the irradiated medium by adding an Auger electron component, it is necessary to determine the change in the microdosimetric spectra brought about by the incorporation of such agents. Using Monte Carlo simulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…In other research, the energy deposition due to secondary electrons produced from GNPs and the microscopic dose enhancement around GNPs were quantified (Jones et al, 2010). The MC results obtained by McMahon (McMahon et al, 2011;Lechtman et al, 2011Lechtman et al, , 2013Garnica-Garza et al, 2013) are in good agreement with experimentally observed cell killing by the combination of X-rays and GNPs. In an experimental study (Rahman et al, 2009) where kilovolt X-ray radiation and megavolt electron radiation were used in the presence of GNPs in bovine aortic endothelial cells, it was found that the cell damage increases with the increase in the GNP concentration.…”
Section: Introductionsupporting
confidence: 66%
“…In other research, the energy deposition due to secondary electrons produced from GNPs and the microscopic dose enhancement around GNPs were quantified (Jones et al, 2010). The MC results obtained by McMahon (McMahon et al, 2011;Lechtman et al, 2011Lechtman et al, , 2013Garnica-Garza et al, 2013) are in good agreement with experimentally observed cell killing by the combination of X-rays and GNPs. In an experimental study (Rahman et al, 2009) where kilovolt X-ray radiation and megavolt electron radiation were used in the presence of GNPs in bovine aortic endothelial cells, it was found that the cell damage increases with the increase in the GNP concentration.…”
Section: Introductionsupporting
confidence: 66%
“…It has been reported that a secondary dose enhancement effect may result from the production of Auger electrons. 11 The low energy Auger electrons produced in the gold are able to travel beyond the extent of the GNP and cause ionization damage to the cell region to which the gold is attached (typically cell membrane, cytoplasm region, or cell nucleus, depending on the size of the individual GNP).…”
Section: Introductionmentioning
confidence: 99%
“…This change, in principle, would be beneficial in terms of the TCP as the high linear energy transfer of the electron cascade released from the high-atomic number atoms in the contrast agent would result in an increased lethality. 24 As the radiobiological parameters needed to account for the presence of the contrast agent in the GTV are not known, it is not possible to estimate the TCP for the treatment plans modeled in this work. We have shown, however, that when combining high-energy and CERT treatments, the OARs are receiving even lower maximum doses than when no contrast agent was used as part of the treatment.…”
Section: Discussionmentioning
confidence: 99%